2019
DOI: 10.1093/gerona/glz108
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K Status and Mobility Limitation and Disability in Older Adults: The Health, Aging, and Body Composition Study

Abstract: Abstract Background Vitamin K has been implicated in chronic diseases associated with increased risk for mobility disability, such as osteoarthritis and cardiovascular disease. However, the association between vitamin K status and mobility disability is unknown. Therefore, we examined the association between vitamin K status and incident mobility disability in the Health, Aging, and Body Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
(35 reference statements)
0
12
0
Order By: Relevance
“…Subsequent analysis of the Health ABC study showed that subjects (n = 1323; mean age 74.2 ± 2.8 years) with plasma phylloquinone level < 0.5 nmol/L were more likely to develop mobility limitations and disability, compared to those with at least 1.0 nmol/L plasma phylloquinone. On the other hand, plasma uncarboxylated MGP (n = 716) was associated with mobility disability in a non-linear fashion but was not associated with mobility limitation [35]. Shea et al also analysed the prospective data of Health ABC and Osteoarthritis Initiatives and found that adequate circulating phylloquinone level (≥ 1 nmol/L) and 25-hydroxyvitamin D (≥ 50 nmol/L) predicted better short physical performance battery scores and gait speed, in follow-up investigations.…”
Section: Prospective Studiesmentioning
confidence: 88%
See 1 more Smart Citation
“…Subsequent analysis of the Health ABC study showed that subjects (n = 1323; mean age 74.2 ± 2.8 years) with plasma phylloquinone level < 0.5 nmol/L were more likely to develop mobility limitations and disability, compared to those with at least 1.0 nmol/L plasma phylloquinone. On the other hand, plasma uncarboxylated MGP (n = 716) was associated with mobility disability in a non-linear fashion but was not associated with mobility limitation [35]. Shea et al also analysed the prospective data of Health ABC and Osteoarthritis Initiatives and found that adequate circulating phylloquinone level (≥ 1 nmol/L) and 25-hydroxyvitamin D (≥ 50 nmol/L) predicted better short physical performance battery scores and gait speed, in follow-up investigations.…”
Section: Prospective Studiesmentioning
confidence: 88%
“…In terms of mobility, the Health ABC study found that circulating vitamin K level (< 0.5 nmol/L) was associated with mobility limitation and disability, compared to those with a level > 1.0 nmol/L. The uncarboxylated MGP was not associated with both mobility variables [35].…”
Section: Cross-sectional Studiesmentioning
confidence: 97%
“…Vitamin K can suppress NF-kB signal transduction and ROS generation, likely through direct effects on muscle tissue. Older subjects with lower plasma vitamin K seem to retain higher mobility limitation and disability [64,65]. Vitamin D, classically classified as a steroid hormone, is well recognized to be a critical regulator for muscle function during all life spans, from intrauterine to late-phase life, due to anti-inflammatory, metabolic, and immunoregulatory actions, even though its antioxidant effect has been recently debated [66][67][68][69][70][71][72].…”
Section: Inflammaging Gerokines and Antiaging Approachmentioning
confidence: 99%
“…Although no underlying mechanism is proposed, the results suggest the involvement of vitamin K in the disabling process associated with aging. Older adults with lower levels of plasma K1 were found to be more prone to develop mobility limitation and disability, compared to those with higher circulating levels [37]. In a prospective study involving 13 years of follow-up of 644 community-dwelling adults from the Longitudinal Aging Study Amsterdam (LASA) cohort, low baseline vitamin K status (high levels of circulating dp-ucMGP) was associated with a higher frailty index score in older aging people [38].…”
Section: Vitamin K and Health: Evidences From Clinical Studiesmentioning
confidence: 99%
“…Recently, low vitamin K status has been associated with multiple co-morbidities, functional decline, disability and frailty in older adults [37,121], especially in those with associated OA and CVD [11,122]. In addition, inflammation accelerates ageing in individuals with multimorbidity, and further promotes the functional limitation and disability in the elderly [123].…”
Section: Vitamin K In the Interplay Between Calcification And Inflmentioning
confidence: 99%